Electrode modification by diazonium chemistry : studies on the effect of steric bulk on film thickness, and modified activated carbon cloths for energy storage - Subrata, Arnold (Nanyang Technological University, 2021)
The chemical modification of electrode surfaces with organic molecules is an important reaction in electrochemistry. Of the multiple methods which exist for this purpose, aryldiazonium cation reduction is widely considered to be the most popular, due to the high stability of the grafted layer on the surface, as well as the relative ease of the modification procedure. One key disadvantage of grafting by diazonium chemistry is the inherent tendency of the grafted film to bear multilayers of organic molecules, which is not desired in most applications requiring modified electrodes. The side reactions forming these polymeric multilayers are known to occur at vacant, unsubstituted carbons on the aryl ring of the grafted layer. In the first of two broad parts of this thesis, studies were carried out on a glassy carbon (GC) electrode modified with bulky 2,3,5,6-tetramethylaniline (TMA) groups (i.e. GC–TMA), using the precursor to the diazonium salt, 2,3,5,6-tetramethyl-p-phenylenediamine (TMPD). Chapter 2 focuses on the formation of GC–TMA and its extensive characterization using electrochemical and spectroscopic techniques, with the aim of addressing the above problem of multilayer formation since TMPD bears a fully substituted aryl ring, thus preventing the multilayer-forming side reactions due to steric hindrance. The results show that sparse multilayers of TMA groups were observed on GC–TMA instead of the expected monolayer, with an investigation of the possible reasons for the unexpected formation of TMA multilayers. Chapter 3 then explores the same modified electrode further through additional coupling experiments performed on GC–TMA. Various small molecules were conjugated onto the TMA layer of GC–TMA with the intent of ascertaining the feasibility of such coupling, especially given the presence of outward-protruding methyl groups on each TMA moiety. Among these molecules were single-walled carbon nanotubes (SWCNTs), which allowed for the formation of GC–TMA–SWCNT and an assessment of the ability of the tethered SWCNTs to function as molecular wires for both solution-phase and SWCNT-bound species. The second part of the thesis puts the focus on the modification of activated carbon cloth (ACC) electrodes for their use in supercapacitors, such as electric double layer capacitors (EDLCs). Although ACCs have inherently lower porosity and specific surface area than other more commonly preferred carbonaceous materials for EDLCs, they were chosen for the study due to their mechanical stability and flexibility (and hence great potential for use in wearable electronics) while being electrically conductive. In Chapter 4, electrochemically-active anthraquinone (AQ) molecules were attached to predominantly-capacitive ACCs by diazonium chemistry with the aim of increasing the total amount of charge stored and released through faradaic redox reactions. The resulting AQ-modified ACCs saw an increase in the total charge compared to unmodified ACCs, but only at lower scan rates and charge densities in cyclic voltammetry (CV) and galvanostatic charge-discharge (GCD) experiments, respectively. This was found to be due to a combination of the high resistance of the three-electrode cell setups used in our experiments, and the complicated proton-coupled electron transfer (PCET) reactions which AQ molecules undergo.